The structure and properties of single layer and gradient-layered coatings of the Ti-Al-Si-Cr-Mo-S-N system - Ovchinnikov, Stanislav V. (AIP Conference Proceedings)
Using the method of microprobe analysis and transmission electron microscopy, the influence of obtaining conditions upon particular elemental composition and growth structure coatings of Ti-Al-Si-Mo-S-N system was studied. The possibility of formation and characteristics of the structural and elastic-stress state single-layer coatings with nanoscale columnar or equiaxed grains and gradient-layered, combining two types of selected structure, was defined. On the basis of hardness, tribological properties and coating hardness, a conclusion was made about the relative prospects of its use as wear-resistant coatings with a nanocrystalline structure.